Pengaruh Faktor Sosial Ekonomi Karyawan Pelaksana Terhadap Investasi (Biaya Pendidikan) Anak - Chairul Riza Nasution; Yusniar Lubis; Rahma Sari Siregar (Universitas Medan Area, 2019)
The purpose of this study is to know any socio economic factors that affect investment (education costs) of the children of implementing employees at PTPN III Kebun Hulu, Nagori Village, Banjar Hulu, Ujung Padang District, Simalungun Regency. The sampling method is done by Purposive method. The analytical method used is multiple linear regression test with SPSS 18 tools. Socio-economic factors that affect investment (education costs) simultaneously are age, number of children, funds and education on investment (education costs) at PT Perkebunan Nusantara III Kebun Dusun Hulu. This can be seen from the t test, where t-test 2.333 t-table 2.045 at α = 5%. By parsial age variable not have an effect on to invesment ( expense of education) can be seen test of t, where t-hitung (-1,047) t-tabel (2,045), by parsial variable of amount of child not have an effect on to invesment (expense of education) where t-hitung (-1,568) t-tabel (2,045), by parsial earnings of executor employees not have an effect on to invesment (expense of education) where t-hitung (0,180) t-tabel (2,045), by parsial education variable not have an effect on to invesment (expense of education), where t-hitung (0,910) t-tabel (2,045).